Konsekuensi Terhadap Notaris yang Melakukan Tindak Pidana Secara Concursus (Studi Putusan Nomor: 2091/PID.B/2023/PN.SBY) - Desy Damayanti Elisabeth Sitanggang; Alvi Syahrin; Rudy Haposan Siahaan (Jurnal Hukum Lex Generalis, 2025)
The Indonesian Notary Law (UUJN) stipulates that notaries may be held accountable administratively, civilly, and criminally. In District Court Decision Number: 209l/Pid.B/2023/PN.Sby, Notary DC was sentenced to imprisonment of nihil. The research method employed is normative legal research based on literature review, with qualitative analysis of legal principles The findings of this study indicate that Decision Number: 2091/Pid.B/2023/PN.Sby may serve as the basis for dishonorable dismissal of Notary DC, as the criminal acts committed constitute concursus realis in relation to previous court rulings. In sentencing, by applying the rule of the highest penalty plus one-third, namely 7 (seven) years + (A x 7) years = 9 (nine) years and 4 (four) months of imprisonment, the decision fulfills the elements stipulated in Article 13 of the UUJN. This study suggests the need for harmonization between the UUJN and the new Criminal Code regarding sanctions for notaries who commit criminal offenses, greater judicial prudence in sentencing, and clearer provisions within the UUJN on sanctions against notaries.